2008
DOI: 10.1504/ijplm.2008.019971
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reliability and optimal maintenance schedule design: a Life Cycle Cost based approach

Abstract: Customers of industrial system/machines are becoming increasingly focused on life cycle performance of products for their purchase decisions. Manufacturers of such type of products, for example machine tools, are experiencing increased pressure from customers to deliver customised products with documented reliability, maintainability, maintenance and support characteristics and also with minimum environmental impacts. In this article, first the problem has been explored in the context of Indian machine tool in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Though, generally speaking only 15% of the total TCO is consumed during the design and the development phase, research has shown that as much as 85% of the remaining TCO is determined by decisions made during this stage (Lad and Kulkarni, 2008). The early identification of acquisition and ownership costs provides the decision makers with more opportunity of balancing performance, reliability, maintenance support and other goals against life cycle costs by taking documented decisions such as using different levels of automation, redundancies, etc.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…Though, generally speaking only 15% of the total TCO is consumed during the design and the development phase, research has shown that as much as 85% of the remaining TCO is determined by decisions made during this stage (Lad and Kulkarni, 2008). The early identification of acquisition and ownership costs provides the decision makers with more opportunity of balancing performance, reliability, maintenance support and other goals against life cycle costs by taking documented decisions such as using different levels of automation, redundancies, etc.…”
Section: 1mentioning
confidence: 99%
“…The key factor is to find an optimal level of maintenance service in order to be consistent with the organization's objective of attaining minimum total cost (Woodward, 1997). In fact, maintenance offers the opportunity to strongly influence the TCO through different strategies by balancing failure and preventive maintenance costs (Thiede et al, 2012), hence, asset users have great opportunities to evaluate different policies through a cost evaluation (Lad and Kulkarni, 2008). Likewise, decisions on the operative conditions of the asset; its utilization and the production strategies can be supported by the TCO evaluation.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Linderman et al (2005) have shown the economic benefits of jointly considering process control and maintenance decision policies. Lad and Kulkarni (2008) state that failure of machine tool may either stop the machine or lead to poor performance like increased rejections. Pandey et al (2010) presented an approach that considers the effect of rejection cost on optimal maintenance planning decisions.…”
Section: Introductionmentioning
confidence: 99%